Numerical Analysis of the Skew Rolling Process for Rail Axles - Pater Z. (Archives of Metallurgy and Materials, 2015)
The paper describes a new method for producing stepped rail axles. The method is based on the skew rolling process. With this method, the product is formed by three tapered rolls located every 120° on the perimeter of the billet. Positioned askew to the centerline of the billet, the rolls rotate in the same direction and with the same velocity. At the same time, they get closer together or go apart depending on the desired cross sectional reduction of an axle step. In addition, the workpiece is shifted lengthwise relative to the rolls by the translational motion of the workpiece-holding chuck. In order to verify the designed method for producing rail axles, a series of numerical simulations were performed using the Simufact. Forming v.12 simulation software. The numerical modeling enabled the determination of maps of the effective strain and temperature in the finished product as well as variations in the loads and torques during rolling. The numerical results unambiguously confirm that the skew rolling method can be applied to form parts of considerable dimensions (the modeled axles had a length of 2146 mm and their maximum diameter was 202 mm).